Development of mathematical giftedness in the conditions of distance learning - V. I. Glizburg (Acta Biomedica Scientifica)
Background. The article examines the factors of the development of mathematical giftedness in the context of distance learning, depending on the choice of computer mathematical packages and digital platforms. Mathematical giftedness is considered as one of the types of special intellectual giftedness associated with mathematical thinking.The aim. To identify the links between the cognitive structures and types of the mathematical thinking that affect the development of mathematical giftedness, with the specifics of the use of digital resources in distance learning.Materials and methods. The analysis of the features of distance learning and its influence on the development of mathematical giftedness is performed; a comparative study of the relationship between the child’s productive informational activity and the implemented distance learning tools was carried out; methods of selection of digital resources, different in the presented forms and levels of activity of distance work, which contribute to the development of mathematical giftedness of students, have been investigated.Results. The following factors were assigned to the development of mathematical giftedness by means of digital resources: the formation of a child’s productive informational activity; implementation of innovative approaches to teaching; implementation of the methodology for the selection of digital resources. It was found that  the  implementation of mathematical abstractions by digital means of visualization improves the quality of assimilation of concepts, forms a stable interest in the subject, and contributes to the development of topological thinking. The work identifies specific psychological problems arising in the process of implementing distance learning mediated by computer technologies, the resolution of which affects the possibility of developing mathematical giftedness, in particular: the problems of emotional saturation and the construction of interpersonal relationships. As specific factors, contributing to the solution of these problems, the following are proposed, in particular: increasing motivation, designing group tasks, special systems of tasks, implemented according to the principle of engagement, the solution of which leads to competition and cooperation. The understanding of mathematical abstractions is facilitated by computer applications that implement technologies for rendering graphic components.Conclusions. Based on the analysis of cognitive structures and types of mathematical thinking, conclusions are drawn about the specifics of the use of digital resources in the process of distance learning, contributing to the effective development of student’s mathematical giftedness.